OX40L/OX40 Signal Promotes IL-9 Production by Mucosal MAIT Cells During Helicobacter pylori Infection - Ming, Siqi; Zhang, Mei; Liang, Zibin; Li, Chunna; He, Jianzhong; Chen, Peiyu; Zhang, Shunxian; Niu, Xiaoli; Deng, Shimei; Geng, Lanlan; Zhang, Guoliang; Gong, Sitang; et al. (Frontiers in Immunology, 2021)
Mucosal associated invariant T (MAIT) cells are exerting increasingly critical roles in Helicobacter pylori (H. pylori)-induced gastritis by promoting mucosal inflammation and aggravating mucosal injuries. However, the specific mechanism and key molecules involved in are still uncertain. We here identified OX40, a co-stimulatory molecule mainly expressed on T cells, as a critical regulator to facilitate proliferation and IL-9 production by MAIT cells and promote mucosal inflammation in H. pylori positive gastritis patients. Serum examination revealed the increased level of IL-9 in gastritis patients. Meanwhile, OX40 was highly expressed in MAIT cells, and its ligand OX40L was also up-regulated in mucosal dendritic cells (DCs) of gastritis patients, compared with healthy controls. Further results demonstrated that activation of OX40/OX40L promoted IL-9 production by MAIT cells, and MAIT cells exhibited highly-activated and proliferative phenotype after the cross-linking of OX40/OX40L pathway. Moreover, OX40 and OX40L expression, as well as IL-9 level were positively correlated with inflammatory indexes in the gastric mucosa, suggesting the significant roles of OX40 and IL-9 in regulating the mucosal inflammation. Taken together, we elucidated that OX40 promoted MAIT cell-mediated mucosal inflammation in H. pylori-induced gastritis, through enhancing IL-9 production by MAIT cells, which may provide potential targeting strategies for gastritis treatment.